The whole man program : reinvigorating your body, mind, and spirit after 40 - Diamond, Jed. (New York : John Wiley & Sons, Inc., 2002)
This is a breakthrough program for men over 40 and their partners, showing how men can maximize their passion, power, productivity, and purpose. Jed Diamond is an internationally recognized educator and trainer in the areas of men's health, gender issues, and addiction prevention and treatment.
Includes bibliographical references and index.
Keywords: Middle-aged men -- Health and hygiene; Health; Longevity